The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jcm12144714
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Repolarization Markers: Telemonitoring for Chronic Heart Failure Patients

Abstract: Aging and chronic heart failure (CHF) are responsible for the temporal inhomogeneity of the electrocardiogram (ECG) repolarization phase. Recently, some short period repolarization–dispersion parameters have been proposed as markers of acute decompensation and of mortality risk in CHF patients. Some important differences in repolarization between sexes are known, but their impact on ECG markers remains unstudied. The aim of this study was to evaluate possible differences between men and women in ECG repolariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(71 reference statements)
1
1
0
Order By: Relevance
“…The major finding of the present study was confirmation of the association of the Te interval with an increased risk of in-hospital mortality in decompensated patients [17][18][19][20]22,23,43]. Secondly, a significant difference was not observed in ECG repolarization and non-invasive hemodynamic data between HFrEF and HFmrEF patients (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The major finding of the present study was confirmation of the association of the Te interval with an increased risk of in-hospital mortality in decompensated patients [17][18][19][20]22,23,43]. Secondly, a significant difference was not observed in ECG repolarization and non-invasive hemodynamic data between HFrEF and HFmrEF patients (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 75%
“…In particular, it has been previously observed that an increase in the Tpeak-Tend (Te) interval was a risk factor for total and cardiovascular mortality [14][15][16]. An increase in this interval and its short-period temporal dispersion was associated with mortality and decompensation in patients with acute CHF [17][18][19][20][21][22][23]. Finally, non-invasive hemodynamic parameters were studied based on bioimpedance to assess the possibility of monitoring clinical improvements in these patients [19,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%